2010
DOI: 10.1021/jp107434f
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Characterization of Magnesium Bisozonide and Carbonyl Complexes in Solid Argon

Abstract: The reactions of magnesium atoms with dioxygen and dioxygen/carbon monoxide mixture have been investigated by matrix isolation infrared absorption spectroscopy. Magnesium atoms react with dioxygen in solid argon to form the inserted MgO(2) molecules under UV excitation, which were previously characterized. Annealing allows the dioxygen molecules to diffuse and to react with MgO(2) and form the magnesium bisozonide complex, Mg(O(3))(2), which is proposed to be coordinated by two argon atoms in solid argon matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The reaction products of Mg atom with sulfur dioxide in condensing argon or neon will be characterized by matrix infrared spectra and density functional theory calculations, and by comparison to the results from analogous reactions. , Common species, such as SO 2 – and MgO 2 , have been identified in previous papers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction products of Mg atom with sulfur dioxide in condensing argon or neon will be characterized by matrix infrared spectra and density functional theory calculations, and by comparison to the results from analogous reactions. , Common species, such as SO 2 – and MgO 2 , have been identified in previous papers.…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium and its complexes have aroused wide interest in the past few decades. Using matrix-isolation technology, previous studies have shown that the magnesium atom is reactive toward various reagent gases such as O 2 , NO, H 2 , and CH 4 , and both associated complexes and Mg inserted species were reported. The reactivity of some magnesium clusters was also investigated, which indicates that the magnesium dimer is more reactive than a single Mg atom in reactions with methyl halides .…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations in this laboratory on the reactions of metal atoms with dioxygen have shown that the metal atoms reacted with dioxygen to give initially the inserted metal dioxide molecules or metal dioxygen complexes, which further reacted with additional dioxygen in forming various unprecedented oxygen-rich complexes in the experiments with excess oxygen. In this paper, we provide a joint matrix isolation infrared spectroscopic and theoretical study on the reactions of beryllium atoms and O 2 . Two interconvertible beryllium ozonide complexes were prepared and identified, which may serve as ideal models in understanding the mechanism of ozonation in the oxidation reactions at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…Reactions of these dioxide species with a second O 2 molecule lead to MO 4 , an end-on bonded superoxo complex of Ga and In. , Even an oxygen-rich complex was reported for magnesium. A bisozonide complex, Mg(O 3 ) 2 with two equivalent side-on bonded ozonide ligands with D 2 h symmetry was formed via metal atom and dioxygen reactions in solid argon …”
Section: Introductionmentioning
confidence: 99%
“…A bisozonide complex, Mg(O 3 ) 2 with two equivalent side-on bonded ozonide ligands with D 2h symmetry was formed via metal atom and dioxygen reactions in solid argon. 39 Here we report a combined matrix isolation infrared spectroscopic and theoretical study of three oxygen-rich BiO 4 isomers formed by metal atom and dioxygen reactions in solid argon matrix.…”
Section: ■ Introductionmentioning
confidence: 99%